2012
DOI: 10.1049/iet-rpg.2010.0234
|View full text |Cite
|
Sign up to set email alerts
|

Experimental results from the operation of aggregated wave energy converters

Abstract: Experimental results from the operation of aggregated wave energy converters. IET Renewable Power Generation ABSTRACTWave energy comes in pulses and is unsuitable for direct conversion and transmission to the grid. One method to smooth the power is to deploy arrays of wave energy converters (WECs), the geometrical layout and damping optimization of which many have studied analytically and numerically, but very few by experiments at sea. In this paper, the standard deviation of electrical power as function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…4(a) is that the CWR reaches its highest values for the lowest energy period and decreases with increasing energy period. This feature was also seen in the experimental data from the three WEC array in Rahm et al 19 The rectangular array and the single WEC reach a slightly higher CWR than the circle-segment array for all sea states but the difference is small. Figure 4(b) shows a large scattering for the variance as a function of energy period, the variance ranges from 0.15 to 0.41 with an average of 0.23 for the circle-segment array and between 0.49 and 1.06 with an average of 0.64 for the rectangular array.…”
Section: Resultssupporting
confidence: 67%
“…4(a) is that the CWR reaches its highest values for the lowest energy period and decreases with increasing energy period. This feature was also seen in the experimental data from the three WEC array in Rahm et al 19 The rectangular array and the single WEC reach a slightly higher CWR than the circle-segment array for all sea states but the difference is small. Figure 4(b) shows a large scattering for the variance as a function of energy period, the variance ranges from 0.15 to 0.41 with an average of 0.23 for the circle-segment array and between 0.49 and 1.06 with an average of 0.64 for the rectangular array.…”
Section: Resultssupporting
confidence: 67%
“…Although a lot of papers have studied arrays of a few WECs or larger arrays in regular waves, so far, there are few publications on full-scale experiments of WEC arrays, and/or large-scale arrays in irregular waves. In [9], experiments with up to three full-scale point-absorber devices were conducted off-shore at the Swedish west coast. It was shown that the standard deviation of power delivered to the electrical substation reduces with 30% and 80% with two and three WECs, respectively, as a mean for an arbitrary array member.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of reducing fluctuations in wave power parks was considered already in early works on wave energy 1,2 and has received new attention recently, when wave energy is taking the step into full-scale commercial farms. Papers of particular interest for this paper that are treating fluctuations include [3][4][5][6][7][8][9] . Many parameters might affect the performance: the number of devices, the separation between units, the characteristic dimensions of the WECs, geometry of the park, wave climate and incoming wave direction, control strategies, mooring configurations, etc.…”
Section: Introductionmentioning
confidence: 99%